Characterization Of CTP Synthase In Zebrafish (Danio Rerio) - Abdul Wahab, Nurul Wahidah (2019)
CTPS is an enzyme that catalyzes the synthesis of cytidine triphosphate (CTP), one of the four basic nucleotide triphosphates that make up DNA and RNA. CTPS dysregulation has been implicated in many different diseases and cancers. It was also shown previously that CTPS can form filamentous structures called cytoophidia. This structure was found on yeast, fruit flies and human. Nevertheless the mechanism behind cytoophidia formation is still vague. To date, there are no in depth studies yet on characterizing CTPS on Danio rerio (zebrafish) and as there are two CTPS genes in zebrafish i.e ctpsla and ctpslb utilizing zebrafish as model organism can further help to understand the CTPS and its cytoophidia. In this studies, the antibody staining results shows that in developing embryos, CTPS is concentrated on the pronephric duct area and the notochord at the end tail area.